2012
DOI: 10.3892/mmr.2015.3530
|View full text |Cite
|
Sign up to set email alerts
|

Identification of KRAS and PIK3CA but not BRAF mutations in patients with gastric cancer

Abstract: Cetuximab, an immunoglobulin G1 chimeric monoclonal antibody directed against the epidermal growth factor receptor, is currently considered to be the strategy with the most potential for the treatment of gastric cancer due to the low frequency of KRAS mutations in patients with gastric cancer. However, the therapeutic success of cetuximab in colorectal cancer (CRC) has demonstrated that the clinical effect of cetuximab is closely dependent not only on KRAS mutations, but also BRAF and phosphoinositide-3-kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Activating mutation of KRAS is thought to stimulate the RAS/RAF/MEK/signaling pathway independent of EGFR activation. We found the overall KRAS mutation rate was 4.1%, which were close to most of the previous studies in China and Japan (4% - 4.9% in Japan and 4.5% in China) 15, 16, 18. In patients and animal models, the malign function of KRAS G12V mutation has been identified in other tumors, such as colorectal cancer, lung cancer, and pancreatic cancer by multiple techniques 16, 19-25.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Activating mutation of KRAS is thought to stimulate the RAS/RAF/MEK/signaling pathway independent of EGFR activation. We found the overall KRAS mutation rate was 4.1%, which were close to most of the previous studies in China and Japan (4% - 4.9% in Japan and 4.5% in China) 15, 16, 18. In patients and animal models, the malign function of KRAS G12V mutation has been identified in other tumors, such as colorectal cancer, lung cancer, and pancreatic cancer by multiple techniques 16, 19-25.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies indicated that the mutation rate of PIK3CA in GC was 3.8% to 12% 15, 16, 32-35. In our analysis, 3.5% of Chinese GC patients had PIK3CA mutations.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…And gastric cancer patients benefit little from anti- EGFR MoAbs targeted therapy. Compared with colon cancer rectal cancer, KRAS / NRAS / BRAF have a lower mutation rate in gastric cancer, furthermore, there is no consistent conclusion on the role of KRAS / NRAS / BRAF mutations in gastric cancer ( 40 43 ). In this study we found 1 out of 34 gastric cancer cases with BRAF mutation.…”
Section: Discussionmentioning
confidence: 94%